Unraveling Financial Decision Patterns in Family-Owned Startups under Generational Transition - Asrul Jaya; Masruroh; Dharma Widada (Neo Journal of economy and social humanities, 2025)
The intergenerational leadership transition in family-owned startups poses unique challenges in financial decision-making. Unlike established family companies, startups have a more fluid organizational structure and rely on flexibility in dealing with risks and high capital requirements. This study aims to identify patterns of financial decisions during the generational transition process and examine the influence of family dynamics on financial preferences and strategies taken. Using an exploratory qualitative approach, this study was conducted on five family startups in Indonesia that are undergoing a succession process. Data were collected through semi-structured interviews with cross-generational family members involved in finance and leadership functions. The analysis was carried out thematically with a grounded theory approach. The results show that the difference in risk orientation and decision-making horizon between the founding generation and the next generation creates tension as well as opportunities for adaptation. The founding generation tends to maintain internal control and avoid debt, while the new generation is more open to external investors and growth-based financial approaches. This study presents an early model of intergenerational financial dynamics and provides insights for the designers of family-based organizational transition strategies.